Developmental changes of upper airway dimensions in children. Issue 4 (24th February 2020) - Luscan, Romain; Leboulanger, Nicolas; Fayoux, Pierre; Kerner, Gaspard; Belhous, Kahina; Couloigner, Vincent; Garabedian, Erea‐Noël; Simon, François; Denoyelle, Françoise; Thierry, Briac
Abstract: Background: Knowledge about airway dimensions during child growth is of paramount importance for pediatric clinical practice. Decisions about airway management in children are based on relatively limited, imprecise, or incomplete data about airway size. Aims: The aim of this work was to determine the anatomical development and size of airway structures from birth to adolescence using high‐resolution computed tomography scans and to study the correlation between airway measurements and biometric data. Methods: We conducted a retrospective study of all high‐resolution computed tomography scans including the respiratory tract, performed in our tertiary pediatric center (for reasons unrelated to airway symptoms) between June 1, 2016, and October 15, 2017, on children aged from 1 day to 14 years old. On each scan, 23 measurements of the larynx, trachea, and mainstem bronchi were performed. Patients were stratified into 16 groups according to their age. We calculated median value for each measurement in each group. Statistical models were calculated to explore correlation between measurements and age or weight. Results: A total of 192 scans were included (127 boys/65 girls). The mean age was 7 years. The correlations between airway measurements and age or weight were always significant. The relationship between measurements and age was found to be suitably represented by a cubic polynomial equation suggesting that the airway has a rapid growth phase in the first 3 years, followed by a slow growth phase and a second rapid growth phase during adolescence. The most relevant biometric parameter was age concerning 21 of the measurements. Conclusion: This comprehensive anatomical database of upper airway dimensions provides important data in the field of pediatric airway anatomy, particularly relating to the cricoid. We demonstrated that laryngeal, tracheal, and bronchial parameters correlate better to age and have three different growth phases.